EKSPERIMENTASI MODEL CASE METHOD BERBANTUAN E-MODULE TERHADAP HASIL BELAJAR ANALISIS KOMPLEKS DITINJAU DARI PERSEPSI MAHASISWA TERHADAP MATA KULIAH - Udil, Patrisius Afrisno (Jurnal Pendidikan Matematika Unpatti, 2023)
This study aims to find out the influence of the case method learning model assisted by e-module on the learning outcomes of mathematics education students in Nusa Cendana University based on students' perceptions of complex analysis courses. This research is quantitative research with quasi experimental type of research. Population of the study is all the active students, while the sample consist of 106 students consisting of 51 students in the control class who were taught by direct learning model without e-module and 55 students in the experimental class who were taught by case method model with e-module. This research used questionnaire, test, and documentation for collecting the research data. It used two-way ANOVA with different cell for analyzing the data. The result indicates that (1) there is significant difference in the learning outcomes of students who are taught using the case method model assisted by e-module and students who are taught by direct learning models without e-module, (2) there is significant difference in student learning outcomes based on the categories of student perceptions of complex analysis courses, (3) there is no significant difference in student learning outcomes for each group of interaction of learning treatment and student perceptions